2008
DOI: 10.1042/bst0360068
|View full text |Cite
|
Sign up to set email alerts
|

From the common molecular basis of the AAA protein to various energy-dependent and -independent activities of AAA proteins

Abstract: AAA (ATPase associated with various cellular activities) proteins remodel substrate proteins and protein complexes upon ATP hydrolysis. Substrate remodelling is diverse, e.g. proteolysis, unfolding, disaggregation and disassembly. In the oligomeric ring of the AAA protein, there is a conserved aromatic residue which lines the central pore. Functional analysis indicates that this conserved residue in AAA proteases is involved in threading unfolded polypeptides. Katanin and spastin have microtubule-severing acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The role of the pore in the recruitment and extraction of substrates is still contentious. It has been shown that substrates interact with residues in the D2 pore on the distal side of the ring (31,32), and it has been suggested that they are not threaded down the central pore as proposed for other members of the AAA family (33)(34)(35)(36).…”
mentioning
confidence: 99%
“…The role of the pore in the recruitment and extraction of substrates is still contentious. It has been shown that substrates interact with residues in the D2 pore on the distal side of the ring (31,32), and it has been suggested that they are not threaded down the central pore as proposed for other members of the AAA family (33)(34)(35)(36).…”
mentioning
confidence: 99%
“…Here we identify a new FtsH substrate-3-deoxy-D-manno-octulosonate (KDO) transferase-which carries out the attachment of two KDO residues to the lipid A precursor (lipid IV A ) to form the minimal essential structure of the lipopolysaccharide (LPS) (KDO 2 -lipid A). Thus, FtsH regulates the concentration of the lipid moiety of LPS (lipid A) as well as the sugar moiety (KDO-based core oligosaccharides), ensuring a balanced synthesis of LPS.FtsH (HflB) is an ATP-dependent, membrane-bound protease (17, 18) which belongs to the AAA family (ATPases associated with diverse cellular activities) (2,26,31,36). FtsH degrades proteins tagged with the SsrA degradation peptide (12, 13) as well as YccA, SecY, and the ATPase F 0 when they are not complexed (1,20).…”
mentioning
confidence: 99%
“…FtsH (HflB) is an ATP-dependent, membrane-bound protease (17, 18) which belongs to the AAA family (ATPases associated with diverse cellular activities) (2,26,31,36). FtsH degrades proteins tagged with the SsrA degradation peptide (12, 13) as well as YccA, SecY, and the ATPase F 0 when they are not complexed (1,20).…”
mentioning
confidence: 99%
“…Abbreviations used: AAA, ATPase associated with various cellular activities; ER, endoplasmic reticulum; ERAD, ER-associated degradation; MCM, mini-chromosome maintenance; VCP, valosincontaining protein. 1 To whom correspondence should be addressed (email p.freemont@imperial.ac.uk). studies on the AAAs.…”
Section: Introductionmentioning
confidence: 99%